(untitled) (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Malabrigo PL Jr., Eduarte GT, Macandog DM, Maldia LSJ, Pampolina NM, Sotto RC, Buot IE Jr.. 2023. Population survey and red list assessment of Kandelia candel (L.) Druce, a critically endangered mangrove species in the Philippines. Biodiversitas 24: 982-989. Mangroves (particularly the members of the Rhizophoraceae) are viviparous species that produce propagules capable of long-distance dispersal. Hence, endemism in mangroves is not common, as countries share species through currents and wave actions. In the Philippines, it is extremely surprising that Kandelia candel, despite viviparous, is restricted in Baler, Aurora. Furthermore, to determine the real conservation status of the species, we conducted a 100% inventory of all mature individuals in known populations of K. candel in Aurora. Our survey has revealed the natural stands of K. candel have been restricted along the riverbanks of the Zabali and Castillo rivers in Baler, Aurora. The rivers are connected and should be treated as a single population. A total of 1,114 matured individuals have been observed in the two sub-populations. The conservation status of K. candel has been assessed following the categories and criteria set by the International Union for Conservation of Nature (IUCN). Landsat analysis has been conducted to determine the population reduction of the species between 2010 and 2020. The extent of occurrence (EOO) and area of occupancy (AOO) of K. candel have been estimated based on the recorded populations and geo-tagged sampling points during the inventory. The present study result has revealed the least concern status of K. candel for ’Criterion A’; Critically Endangered status for ’Criterion B1 and B2’; and Near Threatened status for ’Criterion C and D’. Accordingly, the overall conservation status of K. candel in the Philippines is assessed here as Critically Endangered (CR B1ab(iii) + B2 ab(iii)).